Information Rights and Social Rights Protection in Kazakhstan's Constitutional Legal Framework - Kobegenova, Gulmira; Seyubergenova, Didar; Ismanov, Taalaibek (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
In this article, the authors examine theoretical approaches and challenges related to the protection of social human rights and the citizens' right to information within the constitutional doctrine of the Republic of Kazakhstan. It has been established that the national regulatory and legal framework governing state bodies' activities is aligned with the fundamental legal principles underlying the state's organization and legal system. The authors analyze the concepts and role of mass media in safeguarding social rights, demonstrating how this enables comprehensive development of institutional openness and social protection of citizens. The authors consider various mechanisms for implementing social rights in the field of legal information and discuss the importance of understanding systemic connections between social security and information rights. The study reveals that the idea of social rights and the right to information emerged from the objective need for people to seek, receive, produce, and disseminate information, as well as a response to excessive secrecy of information essential for civilized society. The authors substantiate the conclusion that while systemic connections between social protection and information rights vary across countries, there is a typical pattern in legislative development. In some foreign countries, these rights arose as elements of freedom of speech and the press. However, in most countries, laws protecting state secrets appeared first, followed by legislative acts guaranteeing the protection of social rights and access to information about the activities of state bodies.